Aplikasi Manajemen Laboratorium Menggunakan Metode MVVM Berbasis Android - Fikri Maulana; Rita Afyenni; Aldo Erianda (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2022)
Information technology plays a major role in all aspects of today's world. Technology can make it easier for humans to manage data quickly and effectively. Especially on android-based data management technology. Because in general people have used Android smartphones. The laboratory is a supporting facility for student practical learning in every department. To support laboratories in the department, an application that can manage damage reporting quickly, procure laboratory equipment, and manage laboratory schedules is needed